2021
DOI: 10.1016/s1473-3099(21)00070-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of an inactivated SARS-CoV-2 vaccine, BBV152: interim results from a double-blind, randomised, multicentre, phase 2 trial, and 3-month follow-up of a double-blind, randomised phase 1 trial

Abstract: Background BBV152 is a whole-virion inactivated SARS-CoV-2 vaccine (3 µg or 6 µg) formulated with a toll-like receptor 7/8 agonist molecule (IMDG) adsorbed to alum (Algel). We previously reported findings from a doubleblind, multicentre, randomised, controlled phase 1 trial on the safety and immunogenicity of three different formulations of BBV152 (3 μg with Algel-IMDG, 6 μg with Algel-IMDG, or 6 μg with Algel) and one Algel-only control (no antigen), with the first dose administered on day 0 and the second do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
287
3
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(335 citation statements)
references
References 30 publications
(26 reference statements)
19
287
3
8
Order By: Relevance
“…32 ). Using the observed neutralization level (a mean of 79.2% of the convalescent titer in that study 33 (Supplementary Table 1), the predicted efficacy of the new vaccine was 79.6% (95% predictive interval: 76.2-83.0%), which is in very close agreement with the reported efficacy of 80.6% (ref. 32 ) and suggests good predictive value of the model (Fig.…”
Section: Estimation Of the Protective Neutralization Level Against Covid-19supporting
confidence: 77%
“…32 ). Using the observed neutralization level (a mean of 79.2% of the convalescent titer in that study 33 (Supplementary Table 1), the predicted efficacy of the new vaccine was 79.6% (95% predictive interval: 76.2-83.0%), which is in very close agreement with the reported efficacy of 80.6% (ref. 32 ) and suggests good predictive value of the model (Fig.…”
Section: Estimation Of the Protective Neutralization Level Against Covid-19supporting
confidence: 77%
“…In the Phase 2 clinical trial, 380 participants were enrolled. 110 This study showed that BBV152-Covaxin has elicited high levels of neutralizing antibodies that remained elevated in all participants 3 months after the second vaccination. No serious adverse events were reported in this study.…”
Section: Safety and Efficacy Of Currently Approved Covid-19 Vaccinesmentioning
confidence: 64%
“…Traditionally, vaccines are either attenuated or inactivated pathogens or protein subunits from the pathogen. As early as 1880, attenuated pathogen vaccines were developed by Pasteur [1], and attenuated virus vaccines now prevent measles, mumps, and rubella [41]. However, attenuating strains takes years, so this type of vaccine cannot be used to tackle the current pandemic, and there are also safety concerns.…”
Section: Current Advances In Covid-19 Vaccinesmentioning
confidence: 99%
“…BBV152 is effective in trafficking antigens to the draining lymph node without systemic circulation and has been demonstrated to be immunogenic, welltolerated, and safe in mice, rats, Syrian hamsters, and nonhuman primates [59][60][61]. A phase 2 clinical trial was successful and BBV152 is now being evaluated in a phase 3 clinical trial (NCT04641481) (Figure 2A) [41]. Inactivated vaccines are generated by chemical or heat stress.…”
Section: Current Advances In Covid-19 Vaccinesmentioning
confidence: 99%